Determinants of Commercial Bank Performance in Transition : An Application of Data Envelopment Analysis - Grigorian, A. David (The World Bank, 2002)
Banking sectors in transition economies have experienced major transformations throughout the 1990s. While some countries have been successful in eliminating underlying distortions and restructuring their financial sectors, in some cases financial sectors remain underdeveloped and the rates of financial intermediation continue to be quite low. Grigorian and Manole estimate indicators of commercial bank efficiency by applying a version of Data Envelopment Analysis (DEA) to bank-level data from a wide range of transition countries. They further extend the analysis by explaining the differences in efficiency between financial institutions and countries by a variety of macroeconomic, prudential, and institutional variables. In addition to stressing the importance of some bank-specific variables, the censored Tobit analysis suggests that: - Foreign ownership with controlling power and enterprise restructuring enhance commercial bank efficiency. - The effects of prudential tightening on the efficiency of banks vary across different prudential norms. - Consolidation is likely to improve efficiency of banking operations. Overall, the results confirm the usefulness of DEA for transition-related applications and may shed light on the optimal architecture of a banking system. This paper--a product of the Private and Financial Sector Development Unit, Europe and Central Asia Region--is part of a larger effort in the region to disseminate the results of research on transition issues. The authors may be contacted at dgrigorian@imf.org or manole@wueconc.wustl.edu